Preliminary study a non-invasion method on early cardiac energy defect based on Hilbert Huang Transform. (November 2020) - Lin, Po-Lin; Chen, Kang-Ying; Ma, Heng; Wang, Chun-Lin; Jen Lin, Yu
Abstract: Statistics released by the World Health Organization in 2018 show that the total death of people is 56.9 million worldwide in 2016. The first one is cardiovascular diseases, including ischemic heart disease and stroke, which accounted for 17.65 million people (31%) [1] . Treadmill Exercise Test is suitable for measuring the changes in Electrocardiography (ECG) initial, middle, and after exercise [2] . They are using it to distinguish chest pain without apparent causes, judging the severity of coronary artery disease, and screening personnel with coronary artery disease risk factors. The most important contribution of this study is to use the Hilbert Huang Transform (HHT) [3], a non-invasive method, to decompose the original ECG signals of inspectors through the Empirical Mode Decomposition (EMD) [4–7], not the commonly used of 12-lead ECG detection method. There is a total of 49 participants in 24 pseudo-positive persons; 4 were re-judged into positive, reducing 83.3% pseudo-positive persons who need to do the follow-up testing, significantly reducing the consumption of medical and time.